Diagnosis and Prevalence (1975–2010) of Sudden Death due to Atlantoaxial Subluxation in Cervical Rheumatoid Arthritis: A Literature Review - Eko Agus Subagio; Pandu Wicaksono; Muhammad Faris; Abdul Hafid Bajamal; Diaz Syafrie Abdillah (The Scientific World Journal)
Rheumatoid arthritis (RA), a chronic inflammatory disease primarily affecting synovial joints and tendons, can potentially impact various organs within the body. One notable complication associated with RA is upper cervical spine instability, medically termed atlantoaxial subluxation (AAS). This condition can lead to adverse consequences, including chronic myelopathy and acute mechanical compression of the medulla oblongata, with the potential for sudden death. While AAS may often remain asymptomatic, some nonspecific symptoms, such as neck pain, have been documented. Severe atlantoaxial subluxation can trigger more distinct symptoms, including delayed occipital pain attributed to the compression of the exiting C2 nerve root. Recent studies have elucidated a spectrum of symptoms preceding sudden death, encompassing vertigo, dizziness, convulsions, dysphagia, disorientation, and seizures. Remarkably, some cases have reported sudden death occurring during sleep. Historical data reveal a fluctuating incidence of this phenomenon, with eleven cases reported between 1969 and 1975 and six cases documented between 1990 and 2010. Notably, one of the most prevalent causes of sudden mortality in individuals with RA is the acute mechanical damage inflicted upon the medulla oblongata due to atlantoaxial subluxation.